Theological Approach in Building an Eco-Friendly Economic Self-reliance Movement (Study of Biogas Installation in the Quran) - Rohmat Dina; Heri Budianto; Sri Suryani (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
Cleanliness is very important in Islam, both physical, environmental, and mental cleanliness that is visible or invisible. It is also recommended to maintain and keep the surrounding environment from dirt to keep it clean. This study aims to find out how the legal nature of biogas and how to use biogas in an Islamic perspective based on the demands of revelation and sunnah and a comparison of the opinions of the scholars. This research is field research. The data collection method used in this study was the observation, interviews were conducted directly to perpetrators of the installation and the community in Sembersari Village, Gedong Tataan District, Pesawaran Regency. The results showed that the process of converting cow dung into biogas through the installation of a biogas digester, not through combustion or processed with fire so that the gas produced from dung or unclean objects is not considered unclean.